Subsurface Interpretation of the Panjang Fault Area, Lampung, Based on Geomagnetic Method - Rasimeng, Syamsurijal; Fahruddin, Fahruddin; Valentin, Ferdio; Aurora, Theressia Githa; Nurlaili, Jesica (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2024)
Research on the area along the Panjang Fault - Lampung, the area from the Teluk Betung to Tanjung Karang Barat area using the 19-T GSM PPM tool with base rover acquisition on 2 tracks 2 kilometers apart obtained 40 acquisition points with a spacing of 0.3 kilometers. This study aims to determine the type of lithology and subsurface rock structure by utilizing the susceptibility value of rocks from magnetic anomalies. In the process of processing magnetic anomaly data, upward continuation is carried out as high as 350 m which is intended to reduce the total anomaly with the upward anomaly results so that a residual anomaly is obtained. Next, make a 2D subsurface model on the incision A - B in the residual anomaly map. Based on the results of qualitative interpretation, the total magnetic anomaly of the research area illustrates positive to negative anomaly values with a tighter contour pattern that indicates the presence of a fault structure. While based on quantitative interpretation, the 2D modeling in incision A - B shows a susceptibility value of 0.100 cgs which can be identified as breccia tuff rock, a susceptibility value of 0.0391 cgs is thought to be rhyolitic tuff rock, pumice tuff rock, and sandstone tuff, and a susceptibility value of 0.150 cgs is a rock from the intrusion of Mount Betung in the form of andesite-basalt lava. In addition, rocks with a susceptibility value of 0.0024 cgs are metamorphic rocks. The correlation between 2D modeling and regional geology is seen in the research area, which is in the Tarahan Formation (Tpot), which is suspected to be a fault structure in the Bumi Waras area with a strike direction of NW - SE which is the course of geothermal manifestations or minerals.